The Level of Nurses Knowledge of Discharge Planning for Pediatric Congenital Heart Disease - Wasfi, Huda; Ajil, Zaid W. (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): To assess the level of nurses' knowledge concerning discharge plan for children with congenital heart diseases and find out the relationship between knowledge and their socio-demographic characteristics.Methods: A descriptive correlational design study was applied on 50 nurses’ who are working at open heart surgery ward in Ibn Al-Nafees Hospital for Cardiovascular Medicine and Surgery and from Ibn Al-Bitar Center for Cardiac Surgery in Baghdad City, Iraq. The study started from September 7th, 2022 to June 7th, 2023, utilizing a non-probability (convenience) sample. The data was collected from nurses through a constructive instrument (Likert scale), and analyzed through the application of descriptive and inferential statistical approaches which applied by using SPSS version 26.0.Results: The results showed that most nurses were female 78% and the majority of them (58%) were between the ages of 20 and 25 years and two-thirds (64%) of nurses held a diploma degree in nursing. Most of nurses (52%) were unmarried and (62%) of them were employees for (1-5) years in nursing in open-heart departments. The findings of the current assessment revealed that nurses have a poor level of knowledge about discharge plans based on the achieved mean score (1.60) for children with congenital heart disease. The study's findings showed an existent statistical relationship between nurses' knowledge and their nursing qualification (P value=0.023).Conclusion: The current study concluded that nurses had a poor level of knowledge, which leads to the inefficiency of the nursing discharge plan and showed a significant relation between nurses' knowledge and their nursing qualification.Recommendation: The study recommended conducting educational program to broaden nurses' knowledge about improve their methods of implementation the discharge plan for children with congenital heart diseases, and thus, improving patient care standard offered by nurses and reducing hospitalization of children.